Effectiveness of a Problem-Based Learning Approach in Clinical Teaching of The Undergraduate Nursing Students: An Integrative Literature Review - Manyisa, Zodwa Margaret; Khunou, Sisinyana Hannah (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Aims: To explore the effectiveness of the (Problem Based Learning) PBL approach in the clinical teaching of undergraduate nursing students Methods: An integrative literature review was used to evaluate the effectiveness of PBL in integrating theory and practice among nursing students in clinical practice. The review searched research articles published in English from 2013 to 2023. Medical Subject Headings (MeSH) guidelines were used to identify relevant search terms, which included PBL. Articles that met the inclusion criteria entailed research articles published in peer-reviewed journals, written in English and the population of undergraduate nursing students. A matrix was developed that outlined (1) characteristics of the study population and (2) challenges affecting the implementation and effectiveness of PBL in clinical teaching. Results: The literature search revealed twenty-one (n=21) studies conducted in various countries. The studies highlighted positive experiences on the effectiveness of the PBL approach in the clinical teaching of undergraduate nursing students. Skills such as critical thinking, problem-solving, and patient diagnosis were attributed to using PBL in the simulation. Conclusion: This paper contributes to the body of knowledge on the effectiveness of the PBL approach in the clinical teaching of undergraduate nursing students. It also contributes to the body of knowledge on PBL in nursing education, particularly in South Africa.